I am Malala: A Woman’s Struggle for Her Rights in Education - Putri Pramesti; Maria Johana Ari Widayanti (Celt: A Journal of Culture, English Language Teaching & Literature, 2019)
The right to experience an education is a basic right for everyone to have. Men and women should have the same opportunities to get a proper education. However, some society seem to differentiate the opportunity for men and women’s education. One of the society that differentiates this is Pakistan. The novel, I Am Malala novel, which is written by Malala Yousafzai is one of those that deals with the inequality of women in education. This article discussed about a research that used qualitative method to describe about woman’s rights in education by using Liberal Feminism. The result of the novel’s analysis showed the struggle of the main character, Malala, who received a number of wrong perceptions from her society, family and tradition about the position of women. The wrong perception became the reason why she suffered from the inequality of education between man and woman.